Media Digital sebagai Sarana Edukasi: Peran Orang Tua Mengoptimalkan Konsumsi Konten Anak - Silalahi, Yetty Novel; Asbari, Masduki; Tambunan, Elsadai Rezeki Uli (AGUSPATI RESEARCH INSTITUTA, 2025)
This study aims to examine the role of parents in optimizing the consumption of children's educational content in the digital age. The method used is a qualitative approach with listen and listen techniques, through the analysis of an interview between Gita Wirjawan and Anggia Kharisma (Chief Content Officer of Visinema Studio) which was published in a YouTube channel entitled